Comparison of absorbed dose measurement using GedOF, nanoDot OSLD and TLD-100 in high radiation level - Abdullah, N.; Mohd Noor, N.; Chelminski, K.; Kamarul Zaman, Z.; Mohammad Zahid, M. (Elsevier, 2025)
Accurate measurement of the absorbed dose in high-radiation environments is crucial to protect human health, optimise medical treatment, and ensure the safety of radiation workers. This study assessed the absorbed dose from two types of Germanium-doped optical fibres (GedOF), namely cylindrical (CGedOF), and flat (FGedOF) shapes, in comparison with commonly used gold standard dosimeters, namely LiF:Mg,Ti (TLD-100), and Al2O3:C (nanoDot OSLD). Prior to the measurement of the absorbed dose, the dosimetric characteristics of each dosimeter were evaluated using 6 MV X-ray and 6 MeV electron beams to establish relevant correction factors. The absorbed doses measured by the Malaysian Secondary Standard Dosimetry Laboratory (SSDL) were compared with the stated doses from the International Atomic Energy Agency (IAEA) using accuracy and efficiency approaches. This evaluation revealed an excellent linear-response relationship among all dosimeters within the intended dose range for both 6 MV X-ray and 6 MeV electron beam, with a coefficient of determination (R2) between 0.992 and 1.000. The sensitivity of the response increased consistently with the dose delivered, except for CGedOF and FGedOF in the 6 MV X-ray beam. At 70 days post-irradiation, CGedOF (24.73 %) exhibited the highest signal fading, followed by FGedOF (23.75 %), TLD-100 (10.25 %), and OSLD (3.00 %). All results of the absorbed dose comparison deviated within the acceptance limits of ±3 %, with the blind test results based on En numbers indicating satisfactory performance according to the ISO 13528 standards. The estimated expanded uncertainties of the absorbed dose measurements for all dosimeters were estimated to be between 2.26 % and 5.58 %, with a coverage factor of k = 2. Our findings confirm the reliability of all tested detectors for accurate absorbed dose measurements in high radiation environments, highlighting potential improvements in radiation safety and medical treatment optimisation.